An in vitro evaluation of the Ca/P ratio for the cytocompatibility of nano-to-micron particulate calcium phosphates for bone regeneration - Liu, Huinan; Yazici, Hilal; Ergun, Celaletdin; Webster, Thomas J.; Bermek, Hakan (Elsevier BV, 2008)
Calcium phosphate based bioceramics have been widely used for orthopedic applications due to their chemical similarity to natural bone. The Ca/P stoichiometry of calcium phosphates strongly influences their performance under biological conditions, which have not yet been fully elucidated to date. For this reason, the objective of this in vitro study was to understand the relationship between the Ca/P ratio of nano-to-micron particulate calcium phosphate substrates and their biological properties, such as osteoblast (bone-forming cell) viability, collagen production, alkaline phosphatase activity and nitric oxide (NO) production. A group of calcium phosphates with Ca/P ratios between 0.5 and 2.5 were obtained by intentionally adjusting the Ca/P stoichiometry of the initial reactants necessary for calcium phosphate precipitation. For samples with 0.5 and 0.75 Ca/P ratios, tricalcium phosphate (TCP) and Ca(2)P(2)O(7) phases were observed. In contrast, for samples with 1.0 and 1.33 Ca/P ratios, the only stable phase was TCP. For samples with a 1.5 Ca/P ratio, the TCP phase was dominant; however, small amounts of the hydroxyapatite (HA) phase started to appear. For samples with a 1.6 Ca/P ratio, the HA phase was dominant. Lastly, for samples with 2.0 and 2.5 Ca/P ratios, the CaO phase started to appear in the HA phase which was the dominant phase. Moreover, the average grain size and the average pore size decreased from micron-scale (e.g. 1370nm for a 0.5 Ca/P ratio) to nano-scale (e.g. 262nm for a 2.5 Ca/P ratio) with increasing Ca/P ratios. The porosity (%) of calcium phosphate substrates also decreased with increasing Ca/P ratios. Previous in vitro results demonstrated increased osteoblast adhesion on calcium phosphates with higher Ca/P ratios (up to 2.5). The present study showed that the collagen production by osteoblasts was similar between all the calcium phosphates but slightly lower with a 1.6 Ca/P ratio. Greater alkaline phosphatase activity by osteoblasts was observed in all the cultures with various calcium phosphates (0.5-2.5 Ca/P ratios) than in the control (only cells in culture). Ca/P ratios of <2 and 1 optimized osteoblast viability and promoted alkaline phosphatase activity in osteoblasts, respectively. However, the presence of the CaO phase in Ca/P ratios 2.0 increased osteoblast NO production and decreased osteoblast viability. In summary, this study provided evidence that the Ca/P ratio of calcium phosphate is a very important factor that should be considered when selecting nano-to-micron particulate calcium phosphates for various orthopedic applications.
Keywords: Calcium Phosphates; Bone Regeneration; Osteoblasts; Biocompatible Materials; Phosphorus; Microspheres; Nanostructures; Rats; Animals, Newborn; Bone Substitutes; Materials Testing; Animals; Calcium; Particle Size; Rats, Wistar; Cells, Cultured